Tendência à depressão baseada em sintomas em atletas subelite - Rêgo, Daianne Cardinalli (2018)
INTRODUCTION: Depression is the most common mood disorder in the world population, and studies indicate that the symptoms of the disorder worsen with the intense practice of physical exercise. Once elite athletes are subjected to factors that trigger depression and they are continually under intense exercise practice, these findings may explain the high prevalence of depression in this population. However, this prevalence in subelite athletes are unknown. OBJECTIVE: To investigate the tendency to depression based on symptoms in subelite athletes. METHOD: The instruments for characterizing the sample and the Beck II Depression Inventory (BDI-II) were answered by 50 athletes, 35 not-sportsmen and 30 sportsmen. Mann-Whitney U tests, Factorial ANOVA with contrast, Pearson's Chi-square and Spearman's correlation were used for statistical analysis, considering p<0.05. RESULTS: Study 1: Subelite athletes showed a tendency to depression lower than not-sportsmen (p<0.000). Among the male participants, subelite athletes exhibited the lowest scores, and a similar result was found among adolescents and young adults. Subelite athletes also presented the best results for all levels of competition (p<0.001). Participants who receive financial aid had less depression symptoms compared to those who do not receive (p=0.010) and not-sportsmen (p<0.001). Moreover, the results regarding the time of participation in competitions (up to 3 years, p=0.003; over 4 years, p<0.001) and the frequency of training per week (up to 3 days, p = 0.001; days, p <0.001) were favorable to athletes. Collective sports athletes presented less mental distress than those of individual sports (p = 0.005) and non-athletes (p <0.001). Furthermore, the tendency to depression was associated and inversely correlated to the condition of being subelite athlete. Study 2: Athletes presented a tendency to depression less than sportsmen (p=0.011). Subelite athletes receiving financial aid have fewer symptoms of depression than those who do not receive (p=0.007) and sportsmen (p=0.001). Subelite athletes who have competed for more than 4 years presented better results and those of collective sports showed less symptoms than individual athletes (p=0.019). In addition, the tendency to depression was associated and inversely correlated to the condition of being a subelite athlete. CONCLUSION: Athletes are less affected by symptoms of depression, presenting minimal vulnerability to the disease. Men have fewer symptoms, especially athletes, and being an athlete seems to be beneficial to adolescents. This lower vulnerability is also directly evidenced by the receipt of financial aid and by the choice of collective sports.